If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 + 2(9x + -4) = 0 Reorder the terms: 6x + 6 + 2(-4 + 9x) = 0 6x + 6 + (-4 * 2 + 9x * 2) = 0 6x + 6 + (-8 + 18x) = 0 Reorder the terms: 6 + -8 + 6x + 18x = 0 Combine like terms: 6 + -8 = -2 -2 + 6x + 18x = 0 Combine like terms: 6x + 18x = 24x -2 + 24x = 0 Solving -2 + 24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 24x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 24x = 0 + 2 24x = 0 + 2 Combine like terms: 0 + 2 = 2 24x = 2 Divide each side by '24'. x = 0.08333333333 Simplifying x = 0.08333333333
| 2b-3-10b-9= | | i(-i)= | | 0.25(8+4x)-0.5(10+2x)= | | 9w+w+8w= | | 3(x-1)+2(4x-5)=(x-3)+5 | | -2(7z+5)=-14z+13 | | 2sin^2x+3sinx+1=0 | | 3n^2-9n-3=0 | | -6w+19=8w+5 | | y+0.6y-1.2=2(y-1.4) | | -12x-14=-2(6x+7) | | h=-1+3l^2+s | | In(x-5)+In(x+6)=1 | | m^2+2mn-3n^2=0 | | X-3y=600 | | x^2+16x+64y^2=0 | | 5c+56=120 | | 9x+10=199 | | 128=3.14(8)(8)h | | 128=3.14(8)squaredh | | 3n+6-6=57-6 | | 44=w(2w-3) | | s=-.5gt+vt | | k^2-4k-24=0 | | Y=(9+4k)x | | 6+3y=-4 | | 2x^2+32x-64=0 | | 25x^2+29x+9=0 | | (2a^4-a)+(a^4+4a+4)=0 | | 2x(3y)z+(-5y)(2z)(-10x)-xyz=a | | 12-f=-25 | | 12a-(-9)=23 |